Stress modifications induced by dimer vacancies in the si(0 0 1) surface: Monte Carlo simulations - Sonnet, Ph; Stauffer, Louise; Kelires, Pantelis C. (My University, 2006)
By means of Monte Carlo simulations, we investigate the local stress modifications induced by dimer vacancies (DVs) in the Si(0 0 1) subsurface layers. In presence of n isolated compact DVs, the sites located below these defect rows are under clearly compressive stress in the third layer and under more and more tensile stress, as n increases, in the fourth layer. At higher DVs densities, analogous trends are observed, but the stress modifications are then slightly extended between the dimer rows. Applying our results to the Ge penetration in Si(0 0 1), we show how the knowledge of the local stress may allow predictions of a given impurity behaviour in the vicinity of the surface, provided that the impurity-defect and impurity–impurity interactions do not play a major role compared to the local stress modification induced by the presence of DVs.
Keywords: Germanium; Silicon; Dimers